Assessment of inpatient paediatric care in first referral level hospitals in 13 districts in Kenya. - English, M; Esamai, F; Wasunna, A; Were, F; Ogutu, B; Wamae, A; Snow, R; Peshu, N (2004)
BACKGROUND: The district hospital is considered essential for delivering basic, cost-effective health care to children in resource poor countries. We aimed to investigate the performance of these facilities in Kenya. METHODS: Government hospitals providing first referral level care were prospectively sampled from 13 Kenyan districts. Workload statistics and data documenting the management and care of admitted children were obtained by specially trained health workers. FINDINGS: Data from 14 hospitals were surveyed with routine statistics showing considerable variation in inpatient paediatric mortality (range 4-15%) and specific case fatality rates (eg, anaemia 3-46%). The value of these routine data is seriously undermined by missing data, apparent avoidance of a diagnosis of HIV/AIDS, and absence of standard definitions. Case management practices are often not in line with national or international guidelines. For malaria, signs defining severity such as the level of consciousness and degree of respiratory distress are often not documented (range per hospital 0-100% and 9-77%, respectively), loading doses of quinine are rarely given (3% of cases) and dose errors are not uncommon. Resource constraints such as a lack of nutritional supplements for malnourished children also restrict the provision of basic, effective care. INTERPRETATION: Even crude performance measures suggest there is a great need to improve care and data quality, and to identify and tackle key health system constraints at the first referral level in Kenya. Appropriate intervention might lead to more effective use of health workers' efforts in such hospitals.